Herbal Supplements That Have the Potential to Accelerate Recovery of Exercise-Induced Muscle Damage: Systematic Review - Sendy Mohamad Anugrah; Nining Widyah Kusnanik; Endang Sri Wahjuni; Heryanto Nur Muhammad; Soni Sulistyarto; Bambang Purwanto; Dadan Resmana; Agung Dwi Juniarsyah; Novadri Ayubi; Eka Sari (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
This study aims to analyze herbal supplements that have the potential to accelerate recovery from exercise-induced muscle damage through a systematic review. Article searches were carried out using electronic databases originating from Pubmed and Scopus published from 2019 to 2022 using the keywords herbal, curcumin, garlic, ginger, tribulus, cinnamon, biomarkers, muscle pain, inflammatory markers, and antioxidant effects. The inclusion criteria in this literature review resulted in 14 selected articles resulting from a screening process of 90 articles. The results presented in this literature review reveal the fact that there are significant changes related to EIMD after consuming herbal supplements from 14 selected articles with doses varying between 500-2000 grams per day. In addition, other results showed that intervention with herbal products affected biomarkers and oxidative stress. Therefore, this systematic review provides evidence that supplemental intake strategies are essential for the average athlete or individual to minimize the negative effects of strenuous and excessive training. This systematic review concluded that herbal ingredients such as cinnamon, curcumin, garlic, ginger, and tribulus terrestris may help athletes or individuals recover from EIMD.